ANALISIS DAMPAK KEBIJAKAN PERIODISASI KEPALA SEKOLAH - S Sukari (MAMBA'UL 'ULUM, 2022)
Purposes of the research are to reveal and to analyze clearly and carefully about: (1) internal and external factors of SWOT analysis of SMK Muhammadiyah 1 of Surakarta that had led it to achieve ISO 9001-2000 certificate, (b) attempts that had been performed by SMK Muhammadiyah 1 of Surakarta that made it to achieve ISO 9001-2000 certificate, (c) implementation of TQM values of SMK Muhammadiyah 1 of Surakarta so that it had achieved ISO 9001-2000 certificate. The research is a case study one. Object of the research is implementation of total quality management (TQM) in SMK Muhammadiyah 1 of Surakarta. Qualitative method is used to analyze data obtained from observations, interview, and photograph documentation. Then, the data is analyzed qualitatively and descriptively. Based on the problem statements, results of the research, and discussion of the research, it can be concluded that SWOT analysis in SMK Muhammadiyah 1 of Surakarta revealed: (1) Strengths that the vocational school has are its policy of School Based Management (MPMBS), it had ISO 9001-2000 certificate, its strategic location, its adequate education facilities and infrastructure, and its human resources that are potential enough. (2) Weaknesses that the vocational school has are its insufficient fund to meet all requirements, there are some teachers/employees who are difficult to accept changes toward improvements, and as partner of vocational schools, industrial/business world has inadequate participation in helping them to provide apprenticeship places and employments for students of vocational schools. (3) Opportunities that the vocational school has are: the increased demands of public, and there is a freedom for a vocational school to develop its own curriculum that suitable with needs of market. (4) Threats that the vocational school faces are development of science and technology especially there is a gap between needs of labor markets and existing learning systems of vocational schools, and limited job opportunities that suitable with existing vocational programs. Attempts that had been performed by SMK Muhammadiyah 1 of Surakarta in achieving ISO 9001-2000 certificate were in line with socialization and implementation of TQM values through several stages, namely, preparation stage, implementation stage and stage of achieving ISO 9001-2000 certificate and post-certification stage in which continuous system improvements should be performed. Generally, the TQM values can be implemented well in SMK Muhammadiyah 1 of Surakarta. Levels of obsession to quality and teamwork were in good criteria, whereas level of focus to customer, education and training, and level of involvement and empowerment of employees that can be implemented were in good criteria.